2021
DOI: 10.5964/ejop.2115
|View full text |Cite
|
Sign up to set email alerts
|

Shame and self-esteem: A meta-analysis

Abstract: Scholars agree that shame has many effects related to psychological functioning declines, and one among others is the fluctuation of self-esteem. However, the association between shame and self-esteem requires further studies. Heterogeneity studies due to different measurements, various sample characteristics, and potential missing research findings may result in uncertain conclusions. This study aimed to explore the relationship between shame and self-esteem by meta-analysis to come up with evidence of hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 42 publications
1
13
0
5
Order By: Relevance
“…The subscales of ASPS exhibited a positive and significant relationship with negative self‐esteem. It is consistent with meta‐analysis research on the negative relationship between shame and self‐esteem (Budiarto & Helmi, 2021). Shame is an experience of negative self‐evaluation emotions associated with self‐criticism and self‐depreciation (Elison et al, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…The subscales of ASPS exhibited a positive and significant relationship with negative self‐esteem. It is consistent with meta‐analysis research on the negative relationship between shame and self‐esteem (Budiarto & Helmi, 2021). Shame is an experience of negative self‐evaluation emotions associated with self‐criticism and self‐depreciation (Elison et al, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…A low self-esteem is also often discussed as a consequence of PSP [e.g., (13)]. As feelings of guilt and shame are known to be related to low self-esteem (14), it seems highly plausible to expect self-esteem problems in individuals with PSP. In addition, wounds and scars caused by the PSP also pose a challenge to selfworth, as they are not in line with the general beauty ideal of flawless skin.…”
Section: Introductionmentioning
confidence: 99%
“…The results from previous studies gave a rationale as to why self-esteem and selfcompassion had been chosen to be covariates in this study (Andreassen et al, 2018;Badii et al, 2020;Budiarto & Helmi, 2021;Chisholm & Gall, 2015;Kotera & Rhodes, 2019;Phillips et al, 2019). Pearson correlations found that self-compassion and self-esteem have a significant relationship with all variables except within sex addiction for females specifically, contradicting the findings of Badii et al (2020) and Kotera and Rhodes (2019) who found significant relationships between sex addiction, self-esteem, and self-compassion.…”
Section: Interpretation Of Findingsmentioning
confidence: 63%